Building a safe operative laparoscopy service in a resource-constrained setting: a case seriesAJOG Global Reports at a Glance - Xun Lian, MD; Emilia Selemane, MD; Sibone Mocumbi, MD; Naima Guterriez, MD; Sierra Washington, MD, MSc (AJOG Global Reports)
BACKGROUND: Successful laparoscopic programs in low- and middle-income countries can be difficult to implement because of expensive equipment and limited skills. We describe the establishment of a gynecologic laparoscopic program through collaboration between two hospitals, namely one in New York (a high-income setting) and the other in Mozambique (a low-income setting). OBJECTIVE: This study aimed to evaluate the safety of a gynecologic laparoscopic program through a novel recycling program and collaboration between two hospitals. STUDY DESIGN: This was a prospective cohort study. RESULTS: The patient characteristics, length of stay, and postoperative complications were evaluated. A total of 29 patients were identified. All underwent an operative laparoscopy. The ages ranged from 23 to 52 years. The procedures included 8 ovarian cystectomies, 6 bilateral salpingectomies, 10 hysterectomies, and 4 myomectomies. The majority of patients were discharged on the same day of surgery (19 of 29). There were no conversions to laparotomy or intraoperative blood transfusions. Four patients were lost to follow-up. No postoperative complications were noted up to two months postoperatively. CONCLUSION: This case series provides preliminary evidence that the re-use and recycling of needed instrumentation can be implemented in laparoscopy programs in low-income countries without compromising patient safety. However, larger cohorts are required to be certain.